Computational Linguistics Between the Digitization of the Arabic Language and the Knowledge Society Challenge - Moghith Zerrouki, Leila (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract: Computational Linguistics This science, which attempts to link the science of linguistics and information, in order to deal with the natural language automatically, has made it the main subject of learning and teaching languages as a basis for study and experimentation. The research and studies include many institutes and universities. "These researches and studies meet the broad aspiration of human communication and computerization, so that the computer, stored in the knowledge of nations and its achievements in the management of life and the development of science and technology, is the tool of man to possess his present Key words: computer linguistics, communication, digitization, automated procession.